Protein and Fat Content of Sili Fish (Macrognathus aculeatus) from the Bengawan Solo River - Marisa Fatma, Dwi; Minarno, Eko Budi; Fahruddin, Mukhlis (Journal of Nutrition and Public Health, 2025)
Background: The sili fish (Macrognathus aculeatus), a freshwater fish, is a specialty and a popular side dish in Lamongan's Nasi Boran cuisine. Fish is a good source of animal protein, while its fat content is predominantly unsaturated, which is beneficial as an efficient energy source, as well as for growth and lowering blood cholesterol. Aims: This study aims to determine the protein and fat content of Sili fish in the Bengawan Solo River, Jelakcatur Village, Kalitengah District, Lamongan Regency. Methods: This research is quantitative descriptive. Sili fish samples were taken from three different stations (Plarisan Station, Gangin Station, and Jelak Station). Protein content was determined using the Kjeldahl method and fat content using the acid hydrolysis method. Result: Protein and fat content varied among the three stations. The highest protein content was found at Jelak station at 13.51%, followed by Gangin station at 11.60%, and Plarisan station at 11.38%. The average protein content across the three samples was 12.16%. The highest fat content was also found at Jelak station at 1.01%, followed by Gangin station at 0.72%, and Plarisan station at 0.70%. The average fat content across the three samples was 0.81%. Conclusion: Sili fish samples from Jelak Station had the highest protein (13.51%) and fat (1.01%) content. Overall, Sili fish from all three locations had good protein and fat nutritional content.